HVDC/FACTS for Grid Services in Electric Power Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Electric power systems are headed for a true changing of the guard, due to the urgent need for achieving sustainable energy delivery. Fortunately, the development of new technologies is driving the transition of power systems toward a carbon-free paradigm while maintaining the current standards of quality, efficiency, and resilience. The introduction of HVDC and FACTS in the 20th century, taking advantage of dramatic improvements in power electronics and control, gave rise to unprecedented levels of flexibility and speed of response in comparison with traditional electromechanical devices. This flexibility is nowadays required more than ever in order to solve a puzzle with pieces that do not always fit perfectly. This Special Issue aims to address the role that FACTS and HVDC systems can play in helping electric power systems face the challenges of the near future.